How to balance valuable innovation with affordable access to medicines in Belgium? - Simoens, Steven; Abdallah, Khadidja; Barbier, Liese; Lacosta, Teresa Barcina; Blonda, Alessandra; Car, Elif; Claessens, Zilke; Desmet, Thomas; De Sutter, Evelien; Govaerts, Laurenz; Janssens, Rosanne; Lalova, Teodora; et al. (Frontiers in Pharmacology, 2022)
BACKGROUND: Countries are struggling to provide affordable access to medicines while supporting the market entry of innovative, expensive products. This Perspective aims to discuss challenges and avenues for balancing health care system objectives of access, affordability and innovation related to medicines in Belgium (and in other countries). METHODS: This Perspective focuses on the R&D, regulatory approval and market access phases, with particular attention to oncology medicines, precision medicines, orphan medicines, advanced therapies, repurposed medicines, generics and biosimilars. The authors conducted a narrative review of the peer-reviewed literature, of the grey literature (such as policy documents and reports of consultancy agencies), and of their own research. RESULTS: Health care stakeholders need to consider various initiatives for balancing innovation with access to medicines, which relate to clinical and non-clinical outcomes (e.g. supporting the conduct of pragmatic clinical trials, treatment optimisation and patient preference studies, optimising the use of real-world evidence in market access decision making), value assessment (e.g. increasing the transparency of the reimbursement system and criteria, tailoring the design of managed entry agreements to specific types of uncertainty), affordability (e.g. harnessing the role of generics and biosimilars in encouraging price competition, maximising opportunities for personalising and repurposing medicines) and access mechanisms (e.g. promoting collaboration and early dialogue between stakeholders including patients). CONCLUSIONS: Although there is no silver bullet that can balance valuable innovation with affordable access to medicines, (Belgian) policy and decision makers should continue to explore initiatives that exploit the potential of both the on-patent and off-patent pharmaceutical markets.